Megemlékezés Hüttl Tivadarról - Hüttl, Tivadar (Gerundium, 2015)
MY GRANDFATHER, PROFESSZOR TIVADAR HÜTTL. he commemoration speech was told by the grandson of Tivadar Hüttl, Tivada Hüttl Junior in 2013 at the unveiling of the professor’s sculpture in the sculpture park in the Medical Central at the Debrecen University. His son and grandson, bearing the same name, have become doctors and the love for this profession gave them strength. Hardly any heirloom or family stories remained for the descendants.